2000
DOI: 10.1111/j.1572-0241.2000.02363.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal associations between coughing or wheezing and acid reflux in asthmatics

Abstract: Background and aims-The pulmonary symptoms of patients with lung disease may be ascribed to gastro-oesophageal reflux although a causal relationship between acid reflux and coughing or wheezing has not been proved. Does cough cause reflux or does reflux cause cough? The aim of this study was to evaluate 24 hour oesophageal pH tracings of asthmatics with gastro-oesophageal reflux to determine the temporal association between acid reflux and coughing or wheezing. Methods-The oesophageal tracings of 128 asthmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Several of the proposed mechanisms whereby GERD can cause respiratory symptoms are similar in asthma and chronic cough and include a vagally mediated reflex, heightened bronchial sensitivity and microaspiration [136]. In a study where the temporal association between coughing or wheezing and reflux episodes in asthmatics was investigated, it was concluded that although occasional coughing can lead to reflux, the reverse is much more common [137]. In that study, almost half of all occasions of coughs and wheezes were associated with reflux.…”
Section: Respiratory Symptomsmentioning
confidence: 96%
“…Several of the proposed mechanisms whereby GERD can cause respiratory symptoms are similar in asthma and chronic cough and include a vagally mediated reflex, heightened bronchial sensitivity and microaspiration [136]. In a study where the temporal association between coughing or wheezing and reflux episodes in asthmatics was investigated, it was concluded that although occasional coughing can lead to reflux, the reverse is much more common [137]. In that study, almost half of all occasions of coughs and wheezes were associated with reflux.…”
Section: Respiratory Symptomsmentioning
confidence: 96%
“…Specifically, a cough that is temporally associated (within 15 minutes) with EBC acidification is highly likely to respond to gastric acid suppression therapy [26•]. Gastroesophageal reflux has been associated unequivocally with respiratory symptoms [4,[27][28][29][30], and there is substantial evidence that acid reflux events most commonly precede the respiratory symptoms [29]. Indeed, although most practicing lung specialists are convinced of the importance of acid reflux to asthma symptoms, they are confused about why the clinical efficacy data for proton pump inhibitors have not been clearly demonstrated [4,30] and remain insufficient for the US Food and Drug Administration to allow these agents to be marketed for respiratory disease.…”
Section: Association Between Airway Acidification and Gastroesophageamentioning
confidence: 99%
“…Gastroesophageal reflux (GER) has been associated unequivocally with respiratory disease [2], and excellent data reveal that acid reflux events most commonly precede the respiratory symptoms [26], suggesting causality. Although most practicing allergists and pulmonologists are convinced of the importance of acid reflux to asthma symptoms, they are confused about why the clinical efficacy data for proton pump inhibition (PPI) are not clearer [27,28], and frustrated by the absence of an objective test to diagnose the condition in their patients [29].…”
Section: Introductionmentioning
confidence: 99%